2021
DOI: 10.3390/biomedicines9080979
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin-Polyvinyl Alcohol Film for Tissue Engineering: A Concise Review

Abstract: The field of biomaterials has been steadily expanding as a large number of pharmaceutical and manufacturing companies invest in research in order to commercialize biomaterial products. Various three-dimensional biomaterials have been explored including film, hydrogel, sponge, microspheres etc., depending on different applications. Thus, gelatin and polyvinyl alcohol (PVA) are widely used as a natural- and synthetic-based biomaterial, respectively, for tissue engineering and clinical settings. The combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 77 publications
0
41
0
2
Order By: Relevance
“…On top of that, current studies on gelatin thin films have demonstrated great potential in tissue engineering and clinical settings. The combination of these materials has proven its synergistic effects in wound-healing applications such as delivering drug to heal a wound in a rat model [ 136 , 137 ]. This is due to good film’s strength required for the wound-healing applications.…”
Section: Discussionmentioning
confidence: 99%
“…On top of that, current studies on gelatin thin films have demonstrated great potential in tissue engineering and clinical settings. The combination of these materials has proven its synergistic effects in wound-healing applications such as delivering drug to heal a wound in a rat model [ 136 , 137 ]. This is due to good film’s strength required for the wound-healing applications.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the use of 3D-bioprinted technology decreases the number of operations necessary for skin replacement. The 3D-shaped bioscaffolds open up new alternatives, such as broadening the range of structures accessible to treat injured skin tissues [ 19 ]. It allows for the precise placement of skin cells to replace damaged skin [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural-based biomaterials are easily accessible, usually non-toxic and non-immunogenic, besides displaying excellent biocompatibility and biodegradability properties, which have been pinpointed ( Table 1 ) [ 19 ]. However, natural-based biomaterials have certain drawbacks due to their weak mechanical strength, without a suitable crosslinker as a supporting component to enhance the stability and assembly of complex structures from the fabricated biomaterials [ 20 ]. Moreover, natural-based biomaterials, particularly collagen has been abundantly found in the extracellular matrix (ECM) of human tissue [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies for applying the biomaterials to cure or treat diseases can be achieved in one of two approaches: either with the features of the nano-scaled materials used, or with the materials as a carrier molecule, to deliver active compounds pharmaceutically to the specific site [ 23 ]. Up until now, researchers have focused on nanoparticle-based biocompatible materials, which are increasingly prevalent and used in a variety of potential biomedical engineering applications, including drug delivery systems [ 24 ], wound healing [ 25 , 26 ], tissue engineering [ 20 , 27 ], dentistry [ 28 , 29 ], cancer therapy [ 30 ] and other related research areas. Despite their interesting applications, research into the use of nanoparticles as biomaterials is also broad [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%